2004
DOI: 10.5194/angeo-22-3537-2004
|View full text |Cite
|
Sign up to set email alerts
|

Detailed dayside auroral morphology as a function of local time for southeast IMF orientation: implications for solar wind-magnetosphere coupling

Abstract: Abstract.In two case studies we elaborate on spatial and temporal structures of the dayside aurora within 08:00-16:00 magnetic local time (MLT) and discuss the relationship of this structure to solar wind-magnetosphere interconnection topology and the different stages of evolution of open field lines in the Dungey convection cycle. The detailed 2-D auroral morphology is obtained from continuous ground observations at NyÅlesund (76 • magnetic latitude (MLAT)), Svalbard during two days when the interplanetary ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 72 publications
(131 reference statements)
8
63
0
Order By: Relevance
“…We shall therefore demonstrate case examples of ion drift and precipitation data obtained during dawn-dusk passes of spacecraft DMSP F13 in both the winter and summer hemispheres. The DMSP observations presented here are a continuation/extension of the preliminary results reported in Sandholt et al (2004) and in Sandholt et al (2006b).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…We shall therefore demonstrate case examples of ion drift and precipitation data obtained during dawn-dusk passes of spacecraft DMSP F13 in both the winter and summer hemispheres. The DMSP observations presented here are a continuation/extension of the preliminary results reported in Sandholt et al (2004) and in Sandholt et al (2006b).…”
Section: Introductionmentioning
confidence: 53%
“…In recent studies we demonstrated the presence of an important extra contribution to the dawn-dusk convection asymmetry and the S-M effect via solar wind -magnetosphere -ionosphere coupling acting on "old open field lines" (Sandholt et al, 2004;Farrugia et al, 2004a;Sandholt et al, 2006b;Sandholt and Farrugia, 2007a,b). This is the few hundred km wide channel of enhanced antisunward convection (our FC 2) which under certain conditions (nonzero IMF B y , ionospheric conductivity gradient) is observed at the dawn/dusk boundaries of the polar cap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galperin (2002) proposed a model that explains the formation of PJ or SAPS during magnetic substorms and storms in the evening-tonighttime sector of the discontinuity region between the auroral electrojets. A detailed consideration of the interrelation between auroral luminosity, FAC and PE during magnetic disturbances in the dayside sector was given by Sandholt et al (2004).…”
Section: Current Systems Of Polar Magnetic Disturbancesmentioning
confidence: 99%
“…CC BY 4.0 License. disturbances was given by Sandholt et al (2004). As shown there, the strong convection channel is located on the dawn side of the polar cap for IMF By>0, and on the dusk side for By<0 conditions.…”
mentioning
confidence: 99%